Sistem Keamanan Sepeda Motor Menggunakan GPS Dan Radio Frequency Identification (RFID) Berbasis Arduino - Herwin Simanjuntak; Rully Pramudita; Nadya Safitri (STMIK IKMI Cirebon, 2020)
Abstract- At this time motorcycle theft cases are still often occur plus the increasing use of motorcycle vehicles, motorcycle theft is caused by the lack of a security system on the ignition which only uses keys and key covers, where security systems like this have been understood mostly motorcycle thieves, the necessity of a motorcycle safety system is needed. To overcome this, a Motorcycle Safety System was made using Arduno-based GPS and Radio Frequency Identification (RFID) to prevent and facilitate the recovery of stolen motor vehicles. The results of this study, the system is made using the Global Positioning System (GPS) as a tool to detect the location of motorcycles, and smart key contacts are added using RFID, SMS gateway and DC-DC Converter.